Regional aspect of the relations of Egypt and Israel under H. Mubarak - Жанатаева, К. Б (Journal of Oriental Studies, 2018)
Egypt became the first Arab country to recognize the sovereignty of Israel. This was a bold decision, which cost Cairo good relations with its neighbors and the USSR. However, the benefits were significant – the return of Sinai and substantial financial support from the US. 37 years ago, on 26 February 1980 y. Egypt and Israel established full diplomatic relations. This was the first example of this kind in the Arab world, as was the previous peace treaty between Cairo and Tel Aviv, concluded on 26 March 1979 y. In the Arab world, both of these events were perceived as «betrayal.» It was committed by the key country in the region, which since the establishment of Israel in the Palestinian territories in 1948 was the leader of the Arab resistance to the «Zionist enemy» and on the territory of which located the headquarters of the League of Arab States (LAS) and the Palestine Liberation Organization (PLO). Coming to power H. Mubarak kept the treaty with Israel, gradually was able to straighten relations with the Arab world. Later it was the Camp David agreements that initiated the negotiation process between Israel and the Arab world.